'I would not be satisfied if I had not given it a try': the expectations and experiences of students in a high school skiing program. Issue 2 (3rd April 2018) - Sisjord, Mari Kristin; Sorensen, Marit
Abstract: The article presents results from a panel study among students who attended a high school program dedicated to the development of athletes in various skiing disciplines. Using the conceptual framework of Bourdieu, the study examined the students' social backgrounds, their expectations of succeeding in the field of skiing as well as in the field of education (secondary school), and the extent to which their expectations were fulfilled. Integral to the latter, were the students' negotiation of uncertainty and realities related to fulfilment of expectations. The investigation was conducted at the first and the third year at school, employing quantitative and qualitative methods. In general, the students came from families with well-educated parents having a distinct sport habitus. During the school period, the students' expectations as to both skiing achievements and good school grades were reduced. Many had experienced challenges. About one-fifth of the sample had quit during the three years and almost one-third had considered quitting at one point. The qualitative interviews revealed how the students managed to adjust and re-evaluate their ambitions, particularly with respect to skiing.